2021
DOI: 10.1002/psp.2513
|View full text |Cite
|
Sign up to set email alerts
|

Spousal absence and well‐being: Evidence from China's internal migration

Abstract: This study analyses the linkage between spousal absence and the well‐being and health of married individuals who are “left‐behind” by a spouse who has migrated away from home for work purposes. As the influence of spousal absence on individual well‐being is underinvestigated, this study contributes to the existing literature by examining the effects for men and women in both rural and urban areas and further explores which group of population may be the most disadvantaged. The analysis is based on data from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 122 publications
(146 reference statements)
0
0
0
Order By: Relevance
“…These personal meanings are a support in times of increased longing and make it easier for partners to maintain a positive attitude toward an LDR (Arditti & Kauffman, 2004). Finally, a recent study demonstrated that the absence of a spouse was negatively associated with the well-being and mental health of left-behind married men and women (Guo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These personal meanings are a support in times of increased longing and make it easier for partners to maintain a positive attitude toward an LDR (Arditti & Kauffman, 2004). Finally, a recent study demonstrated that the absence of a spouse was negatively associated with the well-being and mental health of left-behind married men and women (Guo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%